Nitrile substance polymerization inhibitor, preparation method and application

CN116790040BActive Publication Date: 2026-10-23WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210264583.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-17
Publication Date
2026-10-23
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

[0004]传统阻聚剂均为液相阻聚剂,阻聚效率低、毒性大,且与溶液中单体混合后分离回收难度大,导致阻聚剂用量大,造成更大的经济成本及环境压力;如何创设一种可回收利用,成本低、阻聚效率高的硫铵溶液用阻聚剂,具有十分积极的意义

Benefits of technology

[0037]1、本发明的阻聚剂为固相阻聚剂,可进行回收循环利用,优化现有阻聚剂与溶液中单体混合后分离回收难的局限性,实现了阻聚剂的循环利用;同时该固相阻聚剂在硫铵结晶过程中有助于晶体成型。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003551144110000111
    Figure BDA0003551144110000111
  • Figure HDA0003551144120000011
    Figure HDA0003551144120000011
Patent Text Reader

Abstract

The application discloses a nitrile substance polymerization inhibitor, a preparation method and application, and comprises a temperature-sensitive high polymer modified magnetic functional carrier and a polymerization inhibition component loaded on the carrier, wherein the mass content of the magnetic functional carrier is 20-80 wt% of the total mass of the polymerization inhibitor, and the content of the polymerization inhibition component is 20-80 wt% of the total mass of the polymerization inhibitor; the temperature-sensitive high polymer modified magnetic functional carrier comprises a temperature-sensitive high polymer material, a magnetic component and a nitric acid oxidation furnace slag, and the polymerization inhibition component is a hydroxyl group or nitro group containing aromatic compound; the polymerization inhibitor has good polymerization inhibition effect on nitrile compounds, and the application of the temperature-sensitive high polymer modified magnetic functional carrier makes the polymerization inhibitor easy to recycle and can be recycled; since the sulfur-ammonium solution in the sulfur-ammonium unit of the IPN device contains a large amount of organic nitrile substances, the polymerization inhibitor can be used to solve the blockage problem of the sulfur-ammonium unit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical synthesis, specifically relating to a nitrile polymerization inhibitor, its preparation method, and its application. Background Technology

[0002] Ammonium sulfate has a wide range of applications. In addition to being used as a fertilizer in agriculture, it also has good application prospects in pharmaceutical production, food industry, beer brewing industry, textile industry and other fields.

[0003] There are various methods for industrial production of ammonium sulfate, among which the neutralization method is the most widely used. Taking the methanol-ammonia oxidation process for producing hydrogen cyanide as an example, methanol, ammonia, and oxygen undergo a catalytic reaction to generate a mixed gas containing HCN. Because this mixed gas contains a large amount of unreacted ammonia, it must first be washed with sulfuric acid to dissolve the ammonia, allowing it to react with the sulfuric acid to form an ammonium sulfate solution. The ammonium sulfate solution is then crystallized and dried to obtain ammonium sulfate crystals. In this ammonium sulfate production process, the ammonium sulfate solution contains nitrile substances such as hydroxyacetonitrile and aminoacetonitrile, which are produced by side reactions. Nitriles are chemically very reactive, and changes in temperature or pH can easily induce polymerization. During the evaporation and crystallization of the ammonium sulfate solution, the polymerization of nitrile substances can easily cause blockages in the equipment's pipes, pumps, and filters, severely affecting the operation of the equipment. Therefore, a highly efficient polymerization inhibitor must be added during the ammonium sulfate crystallization process to suppress polymer formation, reduce losses, and ensure the safe and efficient operation of the equipment.

[0004] Traditional polymerization inhibitors are all liquid-phase inhibitors, which have low polymerization inhibition efficiency, high toxicity, and are difficult to separate and recover after mixing with monomers in solution. This results in large amounts of inhibitors being used, causing greater economic costs and environmental pressure. Therefore, it is of great significance to create a recyclable, low-cost, and highly efficient polymerization inhibitor for ammonium sulfate solutions. Summary of the Invention:

[0005] This invention addresses the shortcomings of existing polymerization inhibitor preparation technologies by providing a polymerization inhibitor for nitrile substances in ammonium sulfate solution and its preparation method. This polymerization inhibitor is magnetic and easily recyclable. By incorporating some nitric acid oxidation furnace ash, the polymerization inhibitor's inhibition performance is improved, while simultaneously realizing the resource utilization of furnace ash generated in the nitric acid production process. This invention also provides applications for this polymerization inhibitor, which can be used in ammonium sulfate solution to inhibit the formation of nitrile substances during ammonium sulfate refining.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0007] A nitrile polymerization inhibitor comprises a thermosensitive polymer-modified magnetic functionalized carrier and a polymerization inhibitor loaded on the carrier, wherein the mass content of the magnetic functionalized carrier is 20-80 wt%, preferably 30-70 wt%, of the total mass of the polymerization inhibitor, and the mass content of the polymerization inhibitor is 20-80 wt%, preferably 30-70 wt%, of the total mass of the polymerization inhibitor; the thermosensitive polymer-modified magnetic functionalized carrier comprises a thermosensitive polymer material, a magnetic component, and nitric acid oxidation furnace ash, and the polymerization inhibitor is an aromatic hydrocarbon compound containing hydroxyl or nitro groups.

[0008] The magnetic component includes iron oxide powder.

[0009] In some preferred embodiments of the present invention, the magnetic component in the magnetic functionalized carrier may obviously also include other metallic materials, such as chromium, cobalt, etc. Preferably, the magnetic component is made of inexpensive and readily available iron oxide powder.

[0010] In some preferred embodiments of the present invention, the magnetic functionalized carrier includes a binder, which can be a commonly used polymeric binder in the field of synthesis, such as polyacrylamide, polyamino acids, silane coupling agents, etc. In this invention, considering the selectivity of adsorption of nitrile monomers in ammonium sulfate solution, preferably, the binder is a silane coupling agent with a large specific surface area and strong adhesion. Preferably, the silane coupling agent is a silane coupling agent containing vinyl, amino, epoxy, or methacryloyloxy functional groups.

[0011] In some preferred embodiments of the present invention, the polymerization inhibitor is an aromatic hydrocarbon compound containing hydroxyl or nitro groups, such as phenol, nitrobenzene, hydroquinone, etc.

[0012] In some preferred embodiments of the present invention, the nitric acid oxidation furnace ash is the ash produced by the high-temperature catalysis of the platinum mesh in the oxidation furnace during the ammonia oxidation double-pressure process for producing nitric acid, wherein the content of the precious metal Pt is 5-10%.

[0013] In some preferred embodiments of the present invention, the temperature-sensitive polymer material includes isopropylacrylamide, polyacrylate, etc., and preferably, the temperature-sensitive polymer is isopropylacrylamide, which has a better temperature response.

[0014] In some preferred embodiments of the present invention, in the thermosensitive polymer-modified magnetic functionalized carrier, the mass ratio of the magnetic component to the nitric acid oxidation furnace ash is 10:1-50:1, preferably 15:1-30:1.

[0015] In some preferred embodiments of the present invention, the mass ratio of magnetic component to temperature-sensitive polymer in the magnetic functionalized carrier modified with temperature-sensitive polymer is 0.5:1-2:1.

[0016] A method for preparing a nitrile polymerization inhibitor includes the following steps:

[0017] (1) Dissolve the thermosensitive polymer material in water, disperse the magnetic components and nitric acid oxidation furnace ash in it, add initiator and binder and stir under argon protection, filter, wash and vacuum dry to obtain the thermosensitive polymer modified magnetic functionalized carrier.

[0018] (2) The magnetic functionalized carrier modified with temperature-sensitive polymer is mixed with deionized water in a certain proportion, and then a polymerization inhibitor containing nitro or hydroxyl groups is added. The quaternary ammonium salt is added and the mixture is stirred at constant temperature, filtered and dried to obtain the polymerization inhibitor.

[0019] In this invention, the iron oxide powder in the magnetic component in step (1) may include one or both of γ-Fe2O3 and γ-Fe3O4.

[0020] In this invention, the binder in step (1) is a silane coupling agent. Preferably, the silane coupling agent is a silane coupling agent containing vinyl, amino, epoxy or methacryloyloxy functional groups.

[0021] In this invention, the mass ratio of the magnetic component added in step (1) to the ash slag of the nitric acid oxidation furnace is 10:1-50:1, preferably 15:1-30:1;

[0022] In this invention, in step (1), the mass ratio of magnetic component to temperature-sensitive polymer material is 0.5:1-2:1, and the mass ratio of magnetic component to initiator is 2:1-10:1;

[0023] In this invention, in step (1), the initiator is a peroxide initiator, preferably ammonium persulfate.

[0024] In this invention, in step (1), the mass ratio of the magnetic component to the silane coupling agent is 0.2:1-5:1, preferably 0.5:1-2:1;

[0025] In this invention, the stirring temperature in step (1) is 30-80℃, the stirring time is 0.5-5h, the drying temperature is 70-100℃, and the drying time is 4-8h;

[0026] In this invention, the mass ratio of the thermosensitive polymer-modified functionalized carrier to deionized water in step (2) is 0.5:1-2:1;

[0027] In this invention, in step (2), based on the weight of the carrier / water mixed slurry, the amount of the polymerization inhibitor added is 50-120%, preferably 80-100%;

[0028] In this invention, the quaternary ammonium salt in step (2) is selected from one or more of tetrabutylammonium bromide, benzyltriethylammonium chloride, and benzyltriethylammonium bromide;

[0029] In this invention, the amount of quaternary ammonium salt added in step (2) is based on adjusting the pH of the slurry to 7-10. In this invention, the pH is adjusted by adding quaternary ammonium salt. Under this condition, nitriles can be made more stable and less likely to decompose and produce hydrogen cyanide. At the same time, the addition of quaternary ammonium salt introduces amino groups to the surface of the carrier. The amino groups and Pt groups form stable chelate rings, and the synergistic effect enhances the decomposition and polymerization ability of Pt groups.

[0030] In this invention, the stirring temperature of the polymerization inhibitor slurry in step (2) is 30-80℃, the stirring time is 0.5-5h, and the drying temperature is 70-150℃.

[0031] In this invention, the content of the thermosensitive polymer-modified magnetic functionalized carrier prepared in step (2) is 20-80 wt% based on the total weight of the polymerization inhibitor, preferably 30-70 wt%.

[0032] More preferably, the Fe content accounts for 2-45 wt% of the total weight of the polymerization inhibitor, preferably 20-40 wt%, and the Pt content accounts for 0.02-0.2 wt% of the total weight of the catalyst, preferably 0.5-0.1 wt%. The content of the polymerization inhibitor component is 20-80 wt% based on the total weight of the polymerization inhibitor, preferably 30-70 wt%. The particle size of the polymerization inhibitor is 10-50 μm.

[0033] The present invention also provides the application of the nitrile polymerization inhibitor, which is used in ammonium sulfate solution. It is mainly used to add to the ammonium sulfate solution during the purification of ammonium sulfate. The ammonium sulfate solution is a by-product obtained by the capture of excess raw material ammonia gas by sulfuric acid in the process of producing hydrogen cyanide by methanol ammonia oxidation. The ammonium sulfate solution contains easily polymerizable nitrile substances such as hydroxyacetonitrile produced by the side reaction.

[0034] In the application described in this invention, the amount of polymerization inhibitor added is 50-500 mg / kg ammonium sulfate solution, that is, 50-500 mg of polymerization inhibitor is added per kilogram of ammonium sulfate solution.

[0035] In this invention, the polymerization inhibitor is used to inhibit the polymerization of nitrile substances in ammonium sulfate solution. The method of use and evaluation includes the following steps: adding the polymerization inhibitor to the ammonium sulfate solution (nitrile content 0.1-2%), heating at a constant temperature of 100°C under normal pressure, observing the detailed composition, color and polymer generation of the ammonium sulfate solution as a function of residence time, and evaluating the effect of the polymerization inhibitor; after the evaluation, the polymerization inhibitor is recovered by applying an external magnetic field, and the effect of reuse of the polymerization inhibitor is evaluated.

[0036] Compared with the prior art, the present invention has the following advantages:

[0037] 1. The polymerization inhibitor of the present invention is a solid-phase polymerization inhibitor that can be recycled and reused, which optimizes the limitation of existing polymerization inhibitors that are difficult to separate and recover after mixing with monomers in solution, and realizes the recycling of polymerization inhibitors; at the same time, the solid-phase polymerization inhibitor helps crystal formation during the crystallization process of ammonium sulfate.

[0038] 2. This invention utilizes the ash residue from a nitric acid oxidation furnace. During the high-temperature catalytic process of the nitric acid oxidation furnace, a large amount of nitrogen oxide gas is generated, which plays an in-situ pore-expanding role on the ash residue, giving the furnace ash a porous structure and a large pore size, which is beneficial for the adsorption of nitrile monomers during the polymerization inhibition process. At the same time, the introduction of the noble metal Pt component plays a role in polymer reduction and depolymerization while inhibiting polymerization, further enhancing the polymerization inhibition ability of the polymerization inhibitor.

[0039] 3. In this invention, iron oxide powder is used as the magnetic component. After the ammonium sulfate solution is evaporated and crystallized, the polymerization inhibitor and the ammonium sulfate crystals can be separated under the action of an external magnetic field.

[0040] 4. This invention uses a thermosensitive polymer to functionalize the carrier. The thermosensitive polymer modulates the surface chemical properties of the carrier. During the evaporation of ammonium sulfate solution at a relatively high ambient temperature, the hydrophobicity of the polymerization inhibitor surface helps the nitrile monomers to be adsorbed in time, preventing the polymerization of nitrile monomers. During the cooling process after evaporation at a relatively low ambient temperature, the polymerization inhibitor carrier exhibits a hydrophilic surface, which is conducive to the removal of nitrile monomers, thus achieving the separation of the polymerization inhibitor from the monomers.

[0041] 5. The polymerization inhibitor of the present invention is suitable for inhibiting the polymerization of nitrile substances in ammonium sulfate solution. The polymerization inhibitor has high polymerization inhibition performance and good stability in the temperature range of 20-120℃. Attached image description:

[0042] Appendix Figure 1 This is a schematic diagram illustrating the optimization of polymerization inhibition in the ammonium sulfate solution evaporation crystallization process.

[0043] The system includes: ① oil bath; ② three-necked flask; ③ thermometer; ④ condensation system; and ⑤ tail gas absorption system, including buffer bottle and tail gas absorption bottle. Detailed implementation method:

[0044] The present invention will be described in more detail below with reference to the embodiments, but it should be noted that the following embodiments are not limiting examples of the scope of the present invention.

[0045] In this embodiment, an Agilent Technologies 7890A gas chromatograph was used to quantitatively analyze the nitrile composition, including hydroxyacetonitrile, in ammonium sulfate solution. An FID detector and a DB-5 column were used, with an injection port temperature of 280°C, a detector temperature of 280°C, a carrier gas (nitrogen) flow rate of 3 ml / min, an air flow rate of 400 ml / min, and a hydrogen flow rate of 40 ml / min.

[0046] The furnace ash comes from the oxidation furnace ash of the ammonia oxidation double-pressure nitric acid production unit in Wanhua Chemical Yantai Industrial Park. The furnace ash contains 9wt% Pt, 9wt% Fe, 37wt% Si, and 45wt% O.

[0047] The ammonium sulfate solution came from the hydrogen cyanide unit of Wanhua Chemical's Yantai Industrial Park. This solution is a byproduct obtained from the capture of excess ammonia gas by sulfuric acid in the process of producing hydrogen cyanide via methanol ammoxidation. The ammonium sulfate concentration was 43%, and the specific nitrile components in the solution were: hydroxyacetonitrile 17750 ppm, iminodiacetonitrile 2649 ppm, formamidoacetonitrile 2019 ppm, formamidodiacetonitrile 3239 ppm, and organic formaldehyde 12595 ppm.

[0048] Adopting attachment Figure 1 The apparatus shown evaluates the effect of the polymerization inhibitor of the present invention. A three-necked flask is placed in an oil bath for heating. The three-necked flask is equipped with a thermometer and a condensation system. The condensed water and other light components are refluxed. The upper end of the condenser is connected to a tail gas absorption system, which includes a buffer bottle and an alkaline absorption bottle to recover any toxic gases such as hydrogen cyanide that may escape.

[0049] Isopropylacrylamide, Shanghai Kaiyin Chemical

[0050] Polyacrylate, Jinan Feiyue Chemical

[0051] Example 1

[0052] Dissolve 15g of isopropylacrylamide in water, disperse 30g of iron oxide powder and 2g of furnace ash in it, add 3g of ammonium persulfate and 15g of KH171 vinyltrimethoxysilane (Nanjing Shuguang Chemical), stir under argon protection, filter, wash and vacuum dry to obtain a thermosensitive polymer-modified magnetic functionalized carrier; weigh 30g of the prepared thermosensitive polymer-modified magnetic functionalized carrier and mix it with 15g of deionized water in proportion, add 45g of hydroquinone, add 3.1g of tetrabutylammonium bromide to adjust the pH to 9, stir, filter and vacuum dry to obtain polymerization inhibitor 1#.

[0053] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0054] Comparative Example 1

[0055] Hydroquinone, a common polymerization inhibitor, is designated as polymerization inhibitor 1-1#.

[0056] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0057] Example 2

[0058] Dissolve 20g of isopropylacrylamide in water, disperse 30g of iron oxide powder and 2g of furnace ash in it, add 6g of ammonium persulfate and 30g of KH792 aminopropyltrimethoxysilane coupling agent (Jiangxi Chenguang New Materials), stir under argon protection, filter, wash and vacuum dry to obtain a thermosensitive polymer-modified magnetic functionalized carrier; weigh 30g of the prepared thermosensitive polymer-modified magnetic functionalized carrier and mix it with 20g of deionized water in proportion, add 50g of phenol, add 3.5g of benzyltriethylammonium chloride to adjust the pH to 9, stir, filter and vacuum dry to obtain polymerization inhibitor 2#.

[0059] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0060] Comparative Example 2

[0061] Dissolve 20g of isopropylacrylamide in water, disperse 30g of iron oxide powder in it, add 6g of ammonium persulfate and 30g of KH792 aminopropyltrimethoxysilane coupling agent (Jiangxi Chenguang New Materials), stir under argon protection, filter, wash and vacuum dry to obtain a thermosensitive polymer-modified magnetic functionalized carrier; weigh 30g of the prepared thermosensitive polymer-modified magnetic functionalized carrier and mix it with 20g of deionized water in proportion, add 50g of phenol, add 3.4g of benzyltriethylammonium chloride to adjust the pH to 9, stir, filter and vacuum dry to obtain polymerization inhibitor 2-1#.

[0062] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0063] Example 3

[0064] Dissolve 20g of polyacrylate in water, disperse 30g of iron oxide powder and 1.5g of furnace ash in it, add 6g of ammonium persulfate and 30g of methacryloyloxysilane coupling agent (Nanjing Shuguang Chemical), stir under argon protection, filter, wash and vacuum dry to obtain a thermosensitive polymer-modified magnetic functionalized carrier; weigh 30g of the prepared thermosensitive polymer-modified magnetic functionalized carrier and mix it with 20g of deionized water in proportion, add 55g of nitrobenzene, add 3.5g of benzyltriethylammonium bromide to adjust the pH to 9, stir, filter and vacuum dry to obtain polymerization inhibitor 3#.

[0065] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0066] Comparative Example 3

[0067] Take 30g of iron oxide powder and 1.5g of furnace ash and disperse them in deionized water. Add 30g of methacryloyloxysilane coupling agent (Nanjing Shuguang Chemical). Stir under argon protection, filter, wash and vacuum dry to obtain a magnetic functionalized carrier. Weigh 30g of the prepared magnetic functionalized carrier and mix it with 20g of deionized water in proportion. Add 55g of nitrobenzene and 3.3g of benzyltriethylammonium bromide to adjust the pH to 9. Stir, filter and vacuum dry to obtain polymerization inhibitor 3-1#.

[0068] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0069] Example 4

[0070] Dissolve 60g of isopropylacrylamide in water, disperse 30g of iron oxide powder and 1g of furnace ash in it, add 15g of ammonium persulfate and 60g of 3-glycidyl etheroxypropyltrimethoxysilane coupling agent (Silicon Power Technology), stir under argon protection, filter, wash and vacuum dry to obtain a thermosensitive polymer-modified magnetic functionalized carrier; weigh 30g of the prepared thermosensitive polymer-modified magnetic functionalized carrier and mix it with 60g of deionized water in proportion, add 72g of hydroquinone, add 3.9g of benzyltriethylammonium bromide to adjust the pH to 8, stir, filter and vacuum dry to obtain polymerization inhibitor 4#.

[0071] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0072] Example 5

[0073] Dissolve 60g of isopropylacrylamide in water, disperse 30g of iron oxide powder and 1g of furnace ash in it, add 15g of ammonium persulfate and 60g of 3-glycidyl etheroxypropyltrimethoxysilane coupling agent (Silicon Power Technology), stir under argon protection, filter, wash and vacuum dry to obtain a thermosensitive polymer-modified magnetic functionalized carrier; weigh 30g of the prepared thermosensitive polymer-modified magnetic functionalized carrier and mix it with 60g of deionized water in proportion, add 72g of hydroquinone, add 3.9g of benzyltriethylammonium bromide to adjust the pH to 8, stir, filter and vacuum dry to obtain polymerization inhibitor 5#.

[0074] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 100mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0075] Example 6

[0076] Dissolve 60g of isopropylacrylamide in water, disperse 30g of iron oxide powder and 1g of furnace ash in it, add 15g of ammonium persulfate and 60g of aminopropyltriethoxysilane coupling agent (Jingzhou Jianghan Fine Chemical), stir under argon protection, filter, wash and vacuum dry to obtain a thermosensitive polymer-modified magnetic functionalized carrier; weigh 30g of the prepared thermosensitive polymer-modified magnetic functionalized carrier and mix it with 60g of deionized water in proportion, add 50g of hydroquinone, add 3.9g of benzyltriethylammonium bromide to adjust the pH to 8, stir, filter and vacuum dry to obtain polymerization inhibitor 6#.

[0077] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 300mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0078] Example 7

[0079] After the evaluation experiment of the polymerization inhibitor in Example 6 was completed, the polymerization inhibitor was recovered by applying an external magnetic field. After washing and vacuum drying, the polymerization inhibitor for secondary recycling was obtained and designated as polymerization inhibitor 7#.

[0080] Evaluation of polymerization inhibitor: 150g of ammonium sulfate solution was taken, and the polymerization inhibitor dosage was 200mg / kg of ammonium sulfate solution. The mixture was stirred in an oil bath at 100℃ for 6h to evaluate the polymerization inhibition effect. Gas phase analysis was performed to observe the changes in organic components in the ammonium sulfate solution after the experiment. Simultaneously, the residual ammonium sulfate solution in the filtered flask was used to quantitatively determine the polymer mass.

[0081] Table 1 Evaluation of polymerization inhibition effect of the comparative examples.

[0082]

[0083] As can be seen from the table, compared with traditional liquid-phase polymerization inhibitors (aromatic compounds containing nitro or hydroxyl groups), solid-phase polymerization inhibitors have increased adsorption and depolymerization capabilities for nitrile monomers, significantly improving the polymerization inhibition effect of nitrile monomers. In the evaluation experiment of traditional polymerization inhibitor 1-1#, the content of nitrile substances in the ammonium sulfate solution decreased significantly after the experiment, and the mass of the polymer generated was about 10 times that of the solid polymerization inhibitor.

[0084] The application of nitric acid-oxidized furnace ash can effectively improve the polymerization inhibition effect of nitrile monomers. The porous structure and large pore size of the furnace ash are conducive to the adsorption of nitrile monomers during the polymerization inhibition process. At the same time, the introduction of the noble metal Pt component plays a role in polymer reduction and depolymerization while inhibiting polymerization, further enhancing the polymerization inhibition ability of the inhibitor. In the experiment of polymerization inhibitor 2-1# without adding furnace ash, the polymer generation was 0.12 mg / g ammonium sulfate solution, while in the experiment of polymerization inhibitor 2# modified with furnace ash, the polymer generation was only 0.06 mg / g ammonium sulfate solution.

[0085] Thermosensitive polymer-modified solid-phase polymerization inhibitors modulate the surface chemical properties of the carrier. During the evaporation of ammonium sulfate solution at higher ambient temperatures, the hydrophobicity of the inhibitor surface facilitates the timely adsorption of nitrile monomers, preventing their polymerization. Conversely, during the cooling process after evaporation at lower ambient temperatures, the inhibitor carrier exhibits a hydrophilic surface, which is beneficial for the removal of nitrile monomers, achieving separation of the inhibitor from the monomers. In experiment 3-1# with the inhibitor without the thermosensitive polymer, the polymer formation was 0.11 mg / g ammonium sulfate solution, while in experiment 3# with the thermosensitive polymer-modified inhibitor, the polymer formation decreased to 0.06 mg / g ammonium sulfate solution.

[0086] It can be seen that the amount of solid-phase polymerization inhibitor added has little effect on the polymerization inhibition effect, that is, the polymerization inhibition efficiency of the inhibitor is high, and a good polymerization inhibition effect can be achieved with a low concentration of inhibitor; when comparing inhibitors 4#, 5# and 6#, the amount of polymer generated can all be maintained at a low level.

[0087] When the polymerization inhibitor was recycled and reused, the polymerization inhibition effect of nitriles decreased slightly. In the experiment of polymerization inhibitor #7, the amount of polymer generated increased to about 0.2 mg / g ammonium sulfate solution, but the polymerization inhibition effect was still much higher than that of traditional liquid phase polymerization inhibitors.

Claims

1. A nitrile polymerization inhibitor, characterized in that, The invention comprises a magnetically functionalized carrier modified with a thermosensitive polymer and a polymerization inhibitor loaded on the carrier, wherein the mass content of the magnetically functionalized carrier is 20-80 wt% of the total mass of the polymerization inhibitor, and the content of the polymerization inhibitor is 20-80 wt% of the total mass of the polymerization inhibitor; the magnetically functionalized carrier modified with a thermosensitive polymer comprises a thermosensitive polymer material, a magnetic component, and nitric acid oxidation furnace ash, wherein the polymerization inhibitor is one or more of phenol, nitrobenzene, or hydroquinone; The magnetic component includes iron oxide powder; The temperature-sensitive polymer material includes isopropylacrylamide and polyacrylate; The magnetic functionalized carrier includes a binder selected from polyacrylamide, polyamino acids, and silane coupling agents.

2. The polymerization inhibitor according to claim 1, characterized in that, The binder is a silane coupling agent.

3. The polymerization inhibitor according to claim 2, characterized in that, The silane coupling agent is a silane coupling agent containing vinyl, amino, epoxy, or methacryloyloxy functional groups.

4. The polymerization inhibitor according to claim 1, characterized in that, The magnetic components in the magnetic functionalized carrier also include metallic chromium and / or cobalt.

5. The polymerization inhibitor according to claim 1, characterized in that, The ash from the nitric acid oxidation furnace is the ash produced by the high-temperature catalysis of the platinum mesh in the oxidation furnace during the ammonia oxidation double-pressure nitric acid production process, and contains 5-10% precious metal Pt.

6. The polymerization inhibitor according to claim 1, characterized in that, The thermosensitive polymer is isopropylacrylamide.

7. The polymerization inhibitor according to claim 1, characterized in that, In the thermosensitive polymer-modified magnetic functionalized carrier, the mass ratio of magnetic component to nitric acid oxidation furnace ash is 10:1-50:

1.

8. The polymerization inhibitor according to claim 7, characterized in that, In the thermosensitive polymer-modified magnetic functionalized carrier, the mass ratio of magnetic component to nitric acid oxidation furnace ash is 15:1-30:

1.

9. The polymerization inhibitor according to claim 1, characterized in that, In the magnetic functionalized carrier modified with thermosensitive polymer, the mass ratio of magnetic component to thermosensitive polymer is 0.5:1-2:

1.

10. The polymerization inhibitor according to claim 5, characterized in that, The Fe content accounts for 2-45 wt% of the total weight of the polymerization inhibitor, and the Pt content accounts for 0.02-0.2 wt% of the total weight of the catalyst; the content of the polymerization inhibitor component is based on the total weight of the polymerization inhibitor and is 20-80 wt%.

11. The polymerization inhibitor according to claim 10, characterized in that, The Fe content accounts for 20-40 wt% of the total weight of the polymerization inhibitor, and the content of the polymerization inhibitor component is 30-70 wt% based on the total weight of the polymerization inhibitor.

12. The polymerization inhibitor according to claim 1, characterized in that, The particle size of the polymerization inhibitor is 10-50 μm.

13. A method for preparing a nitrile polymerization inhibitor according to any one of claims 1-12, characterized in that, Includes the following steps: (1) Dissolve the thermosensitive polymer material in water, disperse the magnetic components and nitric acid oxidation furnace ash in it, add initiator and binder, stir under argon protection, filter, wash and vacuum dry to obtain the thermosensitive polymer modified magnetic functionalized carrier. (2) The magnetic functionalized carrier modified with temperature-sensitive polymer is mixed with deionized water, and then a polymerization inhibitor containing nitro or hydroxyl groups is added. Quaternary ammonium salt is added, and the mixture is stirred at constant temperature, filtered, and dried to obtain a polymerization inhibitor.

14. The preparation method according to claim 13, characterized in that, In step (1), the iron oxide powder in the magnetic component includes one or both of γ-Fe2O3 and γ-Fe3O4.

15. The preparation method according to claim 13, characterized in that, The mass ratio of the magnetic component added in step (1) to the ash residue of the nitric acid oxidation furnace is 10:1-50:

1.

16. The preparation method according to claim 15, characterized in that, The mass ratio of the magnetic component added in step (1) to the ash residue of the nitric acid oxidation furnace is 15:1-30:

1.

17. The preparation method according to claim 13, characterized in that, In step (1), the mass ratio of magnetic component to temperature-sensitive polymer material is 0.5:1-2:

1.

18. The preparation method according to claim 13, characterized in that, The mass ratio of magnetic component to initiator is 2:1-10:

1.

19. The preparation method according to claim 13, characterized in that, In step (1), the initiator is a peroxide initiator.

20. The preparation method according to claim 19, characterized in that, In step (1), the initiator is ammonium persulfate.

21. The preparation method according to claim 13, characterized in that, In step (1), the mass ratio of the magnetic component to the binder is 0.2:1-5:

1.

22. The preparation method according to claim 21, characterized in that, In step (1), the mass ratio of the magnetic component to the binder is 0.5:1-2:

1.

23. The preparation method according to claim 13, characterized in that, In step (1), the stirring temperature is 30-80℃, the stirring time is 0.5-5h, the drying temperature is 70-100℃, and the drying time is 4-8h.

24. The preparation method according to claim 13, characterized in that, In step (2), the mass ratio of the thermosensitive polymer-modified functionalized carrier to deionized water is 0.5:1-2:

1.

25. The preparation method according to claim 13, characterized in that, In step (2), the amount of polymerization inhibitor added is 50-120% based on the weight of the carrier / water mixture slurry.

26. The preparation method according to claim 25, characterized in that, In step (2), the amount of the polymerization inhibitor added is 80-100% based on the weight of the carrier / water mixture slurry.

27. The preparation method according to claim 13, characterized in that, In step (2), the quaternary ammonium salt is selected from one or more of tetrabutylammonium bromide, benzyltriethylammonium chloride, and benzyltriethylammonium bromide.

28. The preparation method according to claim 13, characterized in that, In step (2), the amount of quaternary ammonium salt added should be adjusted to adjust the pH of the slurry to 7-10.

29. The preparation method according to claim 13, characterized in that, In step (2), the stirring temperature of the polymerization inhibitor slurry is 30-80℃, the stirring time is 0.5-5h, and the drying temperature is 70-150℃.

30. The preparation method according to claim 13, characterized in that, The content of the thermosensitive polymer-modified magnetic functionalized carrier prepared in step (2) is 20-80 wt% based on the total weight of the polymerization inhibitor.

31. The preparation method according to claim 30, characterized in that, The content of the thermosensitive polymer-modified magnetic functionalized carrier prepared in step (2) is 30-70 wt% based on the total weight of the polymerization inhibitor.

32. The application of the polymerization inhibitor according to any one of claims 1-12 or the polymerization inhibitor prepared by any one of claims 13-31, wherein it is used in ammonium sulfate solution.

33. The application according to claim 32, characterized in that, The polymerization inhibitor is added to the ammonium sulfate solution during the purification of ammonium sulfate.

34. The application according to claim 32, characterized in that, The ammonium sulfate solution is a byproduct obtained by the capture of excess ammonia gas by sulfuric acid in the process of producing hydrogen cyanide by methanol ammoxidation. The ammonium sulfate solution contains nitrile substances produced by the side reaction.

35. The application according to claim 32, characterized in that, The amount of polymerization inhibitor added is 50-500 mg / kg ammonium sulfate solution.

Citation Information

Patent Citations

  • Method for preparing monomer of temperature-sensitive polyisopropylacrylamide

    CN101239927A

  • High-efficiency polymerization inhibitor for acrylonitrile refining

    CN1054973A